VR/AR artworks in the museum: Redefining preservation through collaboration - Stylianou-Lambert, Theopisti; Aristidou, Myrto (My University, 2024)
The rapidly evolving nature of emerging technologies renders artworks made using such technologies a challenging category of objects to be handled by institutions. This paper presents real scenarios of how art made with Virtual Reality (VR) and Augmented Reality (AR) is acquired, exhibited and finally preserved by museums and art institutions, presenting a clear picture of a particular period. Though an extensive body of literature and studies deal with the preservation of ‘New Media’, very few focus on the challenges faced by museums and private institutions when it comes to artworks that use VR/AR.We used in-depth interviews with eight museum professionals working in six key institutions that engage with VR/AR artworks, and four artists, who create such works, in order to define current institutional practices, understand the challenges museum professionals face when dealing with VR/AR artworks, and identify the preservation-related concerns of artists working with these technologies.
Keywords: virtual reality; augmented reality; museums; new media art